Effectiveness of Self-etching Adhesive Only Versus in Combination with Gluma Desensitizer for Preventing Post-composite Sensitivity - A Prospective Study - Hemamalini Rath; Shilpa Mahapatra; Sri Priya Narayanan (Indian Journal of Dental Research)
Introduction: An increase in the incidence of postoperative sensitivity following composite restorations has become an everyday clinical problem. The aim of this study was to evaluate and compare the clinical effectiveness of a self-etching adhesive in combination with a dentin desensitizer (Gluma desensitizer), to a self-etching adhesive only, in preventing post-composite sensitivity immediately and over 30 days following a single topical application. Materials and Methods: This clinical trial included 112 patients (206 teeth), who were randomized to receive self-etching adhesive in combination with Gluma desensitizer or a self-etching adhesive only. The included teeth were tested for tactile, air blast and cold stimuli, following which patients were asked to rate their sensitivity on an 11-point Numeric Rating Scale (NRS). The subjects were then assessed for post-composite sensitivity immediately after, as well as 1 week and 1 month following the treatment. Descriptive statistics were compared using t-test and Chi-square test. Intergroup comparisons of change in NRS scores to various stimuli were compared using the Mann–Whitney U test. Results: The baseline comparison of NRS scores to air, water and tactile stimuli did not reveal any statistically significant differences. The change in NRS scores post air blast, 1 week and 1 month, after the treatment for sensitivity, was observed to be significantly higher in the Gluma group compared to self-etching adhesive (P = 0.001). Conclusion: Subjects belonging to the Gluma desensitizer group reported a statistically significant reduction in postoperative sensitivity to air blast stimuli, following composite restoration, at both 1 week and 1 month follow-up.